FORMULASI DESIGN KEBIJAKAN KARTU PRAKERJA BAGI PENYANDANG DISABILITAS - Hidayatullah, Fajri (BULETIN KONSTITUSI, 2022)
In the 1945 Constitution, it has been emphasized that people with disabilities have the same rights, obligations and positions as other citizens, including in terms of obtaining a pre-employment card, this research focuses on the visually impaired because in terms of making a pre-employment card, there are still some obstacles which are still felt. difficulties in participating in the worker card selection process, To find out the pre-employment card policy for the visually impaired, and To find out the legal umbrella that protects work rights for the visually impaired. This study uses a qualitative descriptive method with data collection techniques sourced from the results of several primary data and secondary data. Primary data comes from interviews, while secondary data comes from books, websites, laws, and journals.